Burden and Depressive Symptoms Associated with Adult-Child Caregiving for Individuals with Heart Failure - SARI, İBRAHİM; SÜNBÜL, MURAT (My University, 2014)
Background . The primary purpose of this study was to investigate adult-child caregiver burden in heart failure (HF) patients. Secondary purpose of the study was to identify the possible influencing factors for caregiver burden and depressive symptoms in a young adult-child caregiver group. Methods . A total of 138 adult-child caregivers and 138 patients with HF participated in this study. Caregivers’ burden, depressive symptoms, and anxiety levels were assessed by using Zarit Caregiver Burden Scale (ZCBS), Beck Depression Inventory, and State-Trait Anxiety Inventory, respectively. Results . The mean ZCBS scores of the female caregivers were significantly higher than male caregivers. Approximately one-third of the adult-child caregivers had at least mild depressive symptoms. Caregivers with higher depressive symptoms had higher levels of caregiver burden. There were positive correlations between caregiving time, severity of depressive symptoms, and perceived caregiver burden. There was a negative correlation between education level of caregivers and perceived caregiver burden. Age, socioeconomic level, and marital status of patients were affecting factors for depressive symptoms in caregivers. Among caregiver characteristics, gender, marital status, and ZCBS scores seem to influence the depression in caregivers. Conclusions . The study findings suggest significant levels of burden and depressive symptoms even in adult-child caregivers of HF patients.